MANAJEMEN PEMBINAAN OLAHRAGA BOLA BASKET PUTRI DI SMA NEGERI 1 JEKULO KUDUS - Safina Naja, Reyna; Priyanto, Priyanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Management is a crucial process in achieving organizational goals, including in sports team management. SMA Negeri 1 Jekulo Kudus is known for its strong achievements in basketball, especially the girls’ team, which actively participates in tournaments at regency and provincial levels. The school implements a structured basketball training program to support athlete development. This qualitative study was conducted with the girls’ basketball team at SMA Negeri 1 Jekulo Kudus, located in Desa Klaling, Jekulo, Kudus. Data was collected through interviews, observations, and documentation, and analyzed descriptively. The research subjects included team administrators, coaches, and athletes. The results show that the management of the girls’ basketball team is well-organized, involving planning, organizing, leading, and controlling. Effective management contributes to the team’s success in various competitions. The study recommends that in the future, the selection of competing athletes should include not only those from Kudus city but also from outside areas to enhance the team’s quality and competitiveness. Thus, the management of the girls’ basketball team at SMA Negeri 1 Jekulo Kudus can continue to improve and achieve greater success.